1999
DOI: 10.1083/jcb.145.4.899
|View full text |Cite
|
Sign up to set email alerts
|

Sulfotransferases of Two Specificities Function in the Reconstitution of High Endothelial Cell Ligands for L-selectin

Abstract: L-selectin, a lectin-like receptor, mediates rolling of lymphocytes on high endothelial venules (HEVs) in secondary lymphoid organs by interacting with HEV ligands. These ligands consist of a complex of sialomucins, candidates for which are glycosylation- dependent cell adhesion molecule 1 (GlyCAM-1), CD34, and podocalyxin. The ligands must be sialylated, fucosylated, and sulfated for optimal recognition by L-selectin. Our previous structural characterization of GlyCAM-1 has demonstrated two sulfation modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
246
1
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(254 citation statements)
references
References 86 publications
(132 reference statements)
6
246
1
1
Order By: Relevance
“…The contribution of L-selectin-dependent homing to the homing overall is Ͼ95% in PLN, Ͼ85% in MLN, and about 50% in PP (30, 44). GlcNAc6ST-2, which is prefer- entially expressed in HEV (25,26), has been established to participate in L-selectin-dependent lymphocyte homing (30). In mice deficient in GlcNAc6ST-2, lymphocyte homing to PLN and MLN is reduced to 50 and 69% compared with wild-type mice, and homing to PP is unchanged (30).…”
Section: Altered Expression Pattern Of Meca-79 Epitope In Hev Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…The contribution of L-selectin-dependent homing to the homing overall is Ͼ95% in PLN, Ͼ85% in MLN, and about 50% in PP (30, 44). GlcNAc6ST-2, which is prefer- entially expressed in HEV (25,26), has been established to participate in L-selectin-dependent lymphocyte homing (30). In mice deficient in GlcNAc6ST-2, lymphocyte homing to PLN and MLN is reduced to 50 and 69% compared with wild-type mice, and homing to PP is unchanged (30).…”
Section: Altered Expression Pattern Of Meca-79 Epitope In Hev Ofmentioning
confidence: 99%
“…GlcNAc6ST-1 mRNA was shown to be expressed in the HEV of mouse lymph nodes (21). Another GlcNAc6ST, GlcNAc6ST-2 (originally named HEC-GlcNAc6ST or LSST and also known as CHST4 and GST-3), has been isolated (25,26). GlcNAc6ST-2 is preferentially expressed in the HEV of lymph nodes (25,26), whereas the expression of GlcNAc6ST-1 is broad (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, mouse and human Fuc-TIV can generate sLe x structures on the surface of CHO cells, but both enzymes differ in their ability to generate sLe x structures of various complexity. It has been shown that CSLEX-1 loses its reactivity when genuine sLe x is modified by sulfate groups (52,53), whereas HECA-452 recognizes sulfated and non-sulfated sLe x equally well (54). It is conceivable that other structural elements further modifying sLe x or the presence of sLe x on more complex oligosaccharides might also selectively abolish CSLEX-1 but not HECA-452 binding.…”
Section: Binding Of Fuc-tiv and Fuc-tvii Transfectants To E-selectin-mentioning
confidence: 99%